1978
DOI: 10.1113/jphysiol.1978.sp012218
|View full text |Cite
|
Sign up to set email alerts
|

Deficient influence of peripheral stimuli on precentral neurones in monkeys with dorsal column lesions.

Abstract: SUMMARY1. Four male monkeys (M. fascicularis) were trained in a movement performance task which involved pulling a horizontal lever into a target zone and then collecting, from one of a variety of positions, a small food reward. The same animals were also trained to sit quietly and accept passive manipulation and natural stimulation of the arm and hand while remaining relaxed.2. After complete bilateral section of the cuneate fasciculi or division of a major part of these dorsal column afferents at C1-C2 or at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 24 publications
5
23
0
Order By: Relevance
“…2). The results were in accord with the report that section of the dorsal column abolished sensory input to the motor cortex [20]. The results altogether provided strong evidence that the motor cortex receives peripheral input directly from the thalamus, but soon controversies arose.…”
supporting
confidence: 81%
“…2). The results were in accord with the report that section of the dorsal column abolished sensory input to the motor cortex [20]. The results altogether provided strong evidence that the motor cortex receives peripheral input directly from the thalamus, but soon controversies arose.…”
supporting
confidence: 81%
“…Early evidence, using evoked potential recordings, showed that the effects on the motor cortex of peripheral stimuli were not abolished by ablation of the somatosensory cortex (Malis, Pribram & Kruger, 1953;Adey, Porter & Carter, 1954). There is also evidence that the fibres responsible ascend in the dorsal columns (Brinkman, Bush & Porter, 1978; Asanuma, Larsen & Yumiya, 1980), a result consistent with the short latencies ofthe effects. The nucleus ventralis posterolateralis, pars oralis (v.p.l.o.)…”
Section: Introductionsupporting
confidence: 59%
“…Further, this property was equally present for both external and internal segment neurones related to either proximal or to distal joint movements. This phasic relationship to specific directions of movement about certain joints has been shown to also occur in motor-sensory cortex neurones by other B. IANSEK AND R. PORTER workers in this laboratory (Lemon et al 1976;Brinkman, Bush & Porter, 1978) and more importantly, this relationship has also been demonstrated for primate substantia nigra neurones (R. Iansek & M. K. Horne, personal observations); suggesting that this is a common feature for basal ganglia nuclei.…”
Section: Discussionmentioning
confidence: 77%